The Scriptures of Israel in Jewish and Christian Tradition : Essays in Honour of Maarten J. J. Menken. - Koet, B. J. (Novum Testamentum, Supplements, 2013)
The Scriptures of Israel in Jewish and Christian Tradition is a collection of studies in honour of Professor Maarten J.J. Menken (Tilburg/Utrecht) and illustrates the rich diversity of approaches to biblical interpretation at the beginning of the Common Era. An international team of specialists share their insights on such topics as the availability of Hebrew, Aramaic and Greek texts, Jewish and Christian hermeneutics, notions of authority and inspiration and even a study of inscriptions. Each in its own way demonstrates that the relationship between text and tradition, culture and belief is always complex.